Biochar application ameliorated the nutrient content and fungal community structure in different yellow soil depths in the karst area of Southwest China - Zhang, Meng; Liu, Yanling; Wei, Quanquan; Gu, Xiaofeng; Liu, Lingling; Gou, Jiulan (Frontiers in Plant Science, 2022)
The influence of biochar on the change of nutrient content and fungal community structure is still not clear, especially in different yellow soil depths in karst areas. A soil column leaching simulation experiment was conducted to investigate the influence of biochar on soil content, enzymatic activity, and fungal community diversity and structural composition. Three biochar amounts were studied, namely, 0%(NB, no biochar), 1.0%(LB, low-application-rate biochar), and 4.0% (HB, high-application-rate biochar). The results showed that biochar increased the pH value and the contents of soil organic matter (SOM), total nitrogen (TN), available phosphorus (AP), and available potassium (AK) but reduced the microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN). Furthermore, this effect was enhanced with increasing biochar amount. Biochar was conducive to improving the nutrient availability in topsoil (0–20 cm), especially TN, AK, and MBN. Meanwhile, biochar affected the enzymatic activity, especially the sucrase activity. Biochar affected the diversity and structure of the fungal community, of which HB treatment had the most obvious effect. Among these treatments, Aspergillus, unclassified_Chaetomiaceae, Mortierella, Spizellomyces, Penicillium, Fusarium, and unclassified_Chromista fungal genera were the highest. Moreover, biochar inhibited the growth of harmful pathogens and increased the abundance of beneficial fungi in soil, and the effect was enhanced with increasing biochar amount and soil depth. Redundancy analysis (RDA) showed that AK was an important factor in yellow soil, although the main environmental factors affecting the fungal community structure were different in different soil depths. Overall, biochar had a positive effect on improving the land productivity and micro-ecological environment of yellow soil in the karst area.